Teori Prilaku Konsumen Islam - Marusnia, Fera Julianti; Nursyahadah, Febby; Hendra, Joni (Al-Sharf: Jurnal Ekonomi Islam, 2024)
This study examines the Islamic Consumer Behavior Theory as an alternative paradigm in understanding the consumption behavior of Muslim society in the modern era. Through a literature review approach, this study aims to analyze the fundamental differences between conventional and Islamic consumer behavior theories, and explore their implications for Muslim consumption patterns. The results of the study indicate that the Islamic consumer behavior theory is based on sharia principles that emphasize the balance between worldly and hereafter interests. Unlike conventional theories that focus on maximizing utility, Islamic theory emphasizes the concept of maslahah (welfare) as the main goal of consumption. Other important findings reveal that the concept of rationality in an Islamic perspective is not only limited to material considerations, but also includes spiritual and ethical aspects. The main conclusion of this study confirms that the Islamic consumer behavior theory offers a more holistic and sustainable approach in understanding the motivations and consumption patterns of Muslim society. The implications of this study have the potential to make a significant contribution to the development of economic policies that are more in line with Islamic values, as well as encouraging more ethical and responsible business practices in the context of the global economy.